2016
DOI: 10.1038/srep29857
|View full text |Cite
|
Sign up to set email alerts
|

Indole-3-carbinol protects against cisplatin-induced acute nephrotoxicity: role of calcitonin gene-related peptide and insulin-like growth factor-1

Abstract: Nephrotoxicity associated with the clinical use of the anticancer drug cisplatin is a limiting problem. Thus, searching for new protective measures is required. Indole-3-carbinol is a powerful anti-oxidant, anti-inflammatory and anti-tumor agent. The present study aimed to investigate the potential protective effect of indole-3-carbinol against cisplatin-induced acute nephrotoxicity in rats. Rats were pre-treated with 20 mg/kg indole-3-carbinol orally before giving cisplatin (7 mg/kg). Cisplatin-induced acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 59 publications
(80 reference statements)
3
12
0
1
Order By: Relevance
“…Normally, it is excreted by the kidneys, primarily by glomerular filtration but also by proximal tubular secretion with little or no reabsorption. If there is deterioration in kidney function, serum level of creatinine rises ( El-Naga, 2014 ; Changizi-Ashtiyani et al, 2016 ; El-Naga and Mahran, 2016 ). Also, concomitant decline in urinary creatinine clearance is observed vis a vis raised serum creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, it is excreted by the kidneys, primarily by glomerular filtration but also by proximal tubular secretion with little or no reabsorption. If there is deterioration in kidney function, serum level of creatinine rises ( El-Naga, 2014 ; Changizi-Ashtiyani et al, 2016 ; El-Naga and Mahran, 2016 ). Also, concomitant decline in urinary creatinine clearance is observed vis a vis raised serum creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al [71] have documented that the combined action of oxidative stress imbalance and autophagy defects causes abnormal cell apoptosis which leads to the occurrence of AKI [71]. Indeed, it is undeniable that the disruption of growth factors and their receptors play a role in CDDP-induced renal injuries [56]. In renal proximal tubular cells, CDDP also activated the EGFR, which is involved in cell death rather than survival under these conditions [73].…”
mentioning
confidence: 99%
“…involve accumulation of potentially toxic compounds in the tubular fluid, which then diffuse into the highly permeable tubular cells (13). Numerous studies have demonstrated that several mechanisms, including oxidative stress, DNA damage and inflammatory responses, mediate cisplatin-induced nephrotoxicity (13,16). The key pathological occurrences in cisplatin-induced nephrotoxicity are renal tubular cell injury and death (14,17).…”
Section: Protein Extracted From Porphyra Yezoensis Prevents Cisplatinmentioning
confidence: 99%